If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+5-5=x+3-5
We move all terms to the left:
2x+5-5-(x+3-5)=0
We add all the numbers together, and all the variables
2x-(x-2)+5-5=0
We add all the numbers together, and all the variables
2x-(x-2)=0
We get rid of parentheses
2x-x+2=0
We add all the numbers together, and all the variables
x+2=0
We move all terms containing x to the left, all other terms to the right
x=-2
| x-2=-10,x= | | 10=2(s+4) | | 2(4-3n)=-5n | | 8−n=5 | | 1+2m-+2=3+m | | f−2/2=2 | | (w+8)=w | | p−3/2=2 | | -3x-2=7(2x+7) | | 24=4x+8,x= | | 5x+2+5x-8=74 | | 24=4x+8x= | | x+2=10,x= | | 4-p=1 | | 6x+10=-4(x-5) | | 4x+5+5x-7=79 | | 3x-5-2x=-4 | | r+15=4r−6 | | 14+2p=-6(1-2p) | | x+5=3/4 | | 3(p−4)=9 | | 4/3x=-2/3 | | 4x+6=8x-8 | | 28=0.57x | | 11^-9x=15^-x-5 | | 173=89-v | | 8q^2-3q=7q^2-5q+48 | | u-0.75=2.6 | | 2x+2(x12)=56 | | X+12(x+12)=56 | | y-9.95=1.59 | | -15-8=-7n-6n |